2021
DOI: 10.3390/jdb9030036
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration in Reptiles Generally and the New Zealand Tuatara in Particular as a Model to Analyse Organ Regrowth in Amniotes: A Review

Abstract: The ability to repair injuries among reptiles, i.e., ectothermic amniotes, is similar to that of mammals with some noteworthy exceptions. While large wounds in turtles and crocodilians are repaired through scarring, the reparative capacity involving the tail derives from a combined process of wound healing and somatic growth, the latter being continuous in reptiles. When the tail is injured in juvenile crocodilians, turtles and tortoises as well as the tuatara (Rhynchocephalia: Sphenodon punctatus, Gray 1842),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…Lizards and the tuatara are able to regenerate large volumes of cartilage tissues in the tail, joints and vertebrae (Alibardi & Sala, 1981; Alibardi & Meyer‐Rochow, 1989, 2021; Alibardi, 2015; Alibardi, 2021; Lozito & Tuan, 2015, 2016a,b). In some geckos, like most lizards not specifically adapted to an arboreal life, the regenerated cartilage is mainly hyaline and the new tail quite stiff (Boring et al, (1948–49); Furieri, 1956; McLean & Vickaryous, 2011; Mufty & Iqbal, 1975; Shah & Chakko, 1968; Werner, 1967).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lizards and the tuatara are able to regenerate large volumes of cartilage tissues in the tail, joints and vertebrae (Alibardi & Sala, 1981; Alibardi & Meyer‐Rochow, 1989, 2021; Alibardi, 2015; Alibardi, 2021; Lozito & Tuan, 2015, 2016a,b). In some geckos, like most lizards not specifically adapted to an arboreal life, the regenerated cartilage is mainly hyaline and the new tail quite stiff (Boring et al, (1948–49); Furieri, 1956; McLean & Vickaryous, 2011; Mufty & Iqbal, 1975; Shah & Chakko, 1968; Werner, 1967).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies (Lozito & Tuan, 2016a,b) shown that the two processes are orchestrated by a different mechanism, (1) the proximal chondrogenesis and mineralization from the activity of BMP‐2 and Ihh while (2) the distal chondrogenesis and mineralization derive from the stimulation of Shh secreted from the regenerating ependyma on the surrounding cells of the blastema. In the regenerating tail cartilage of the tuatara ( Sphenodon punctatus ), differently from that of lizards so far analysed, the calcification of the cartilaginous cylinder occurs centrally and not in outer and inner ring‐like peripheral regions (Alibardi & Meyer‐Rochow, 2019, 2021). The mechanism of this different pattern of growth and calcification remains unexplained but is somehow correlated to the long period of time required for tail regeneration in the tuatara that overlaps with its natural growth (Alibardi & Meyer‐Rochow, 1989, 2019, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to histological and histochemical studies, these investigators also conducted numerous biochemical analyses and enzymatic studies to obtain a broad picture of the metabolism of regenerating tails in geckos and scincid lizards. Several other histological and histochemical studies have been derived from African, Australian, and Caribbean geckos and scincids [ 18 , 19 , 20 , 21 ], and from the New Zealand tuatara [ 11 , 22 , 23 , 24 , 25 ].…”
Section: The Lizard Model: Brief Historical Notesmentioning
confidence: 99%